Erratum: Cooling a mechanical resonator with nitrogen-vacancy centres using a room temperature excited state spin–strain interaction - E. R. MacQuarrie (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14358 (2017); Published 6 February 2017; Updated 29 November 2017. This Article contains a typographical error in the sentence preceding Eq. 4. This sentence should read, ‘Under the secular approximation and working in the limit , the dynamical equation for the phonon occupancy can be simplified to’; that is, with a much-less-than symbol rather than a much-greater-than symbol.